Linear Algebra Education in University: A Literature Review - Supriyadi, Edi; Hussain, Amil; Yasir, Yasir (International Journal of Applied Learning and Research in Algebra, 2024)
The objective of this study is to conduct a thorough literature review in order to give a comprehensive understanding of the opportunities and challenges associated with the teaching and learning of linear algebra in university environments. The review assesses the pedagogical strategies used by academic institutions to enhance student engagement and comprehension, along with the application of linear algebra. We conducted a four-stage process to analyze five articles indexed in Scopus. The review emphasizes the importance of incorporating technology and real-world applications into linear algebra instruction to promote student motivation and active learning. It underscores the necessity of pedagogical approaches that promote student agency, particularly in online learning environments, where traditional teaching practices frequently persist. Exploring the correlation between learning outcomes and semantic networks, evaluating the impact of online platforms on student participation and agency, and evaluating real-world applications for teaching linear algebra are all potential future research directions.